Anthropometrical profile and bio-motor abilities of young elite wrestlers - Jafari Rahmat, A.; Damirchi, A.; Mirzaei B.; Nobari, H. (Physical Education of Students, 2016)
Aim: This study investigated the association between motor performance and somatic type, anthropometric, body composition, physiologic and physical fitness profile in young wrestlers. Material: 16 young wrestlers aging 16-19 with a 4-year-experience of taking part in national championships were selected for the study. Following the standard methods in the testing center of Alborz province some tests like aerobic power, muscular endurance, flexibility and agility speed tests and 1RM were taken to integrate the participants. Also, it should be noted that the participants` height, weight, the girth of thigh, elbow, calf and arm and skin thickness were measured. Results: Somatotype, Somatotype Attitudinal Distance (SAD), Height Weight ratio (HWR) were calculated according to Carter and Heath anthropometric method. Body Fat Percentage (%BF), HWR and SAD resulted in 10.90±1.64, 43.27±0.87 and 0.94±0.87 respectively. Somatotype Standard Deviation and mean regarding endomorphic, mesomorphic and ectomorphic components were 2.16±0.46, 5.20±0.77 and 2.88±0.64 respectively. Physiologically, wrestlers VO2MAX (kg/min) were 49.31±4.22 and their Resting Heart Rate (bpm) were 68.31±6.64. Conclusion: As the present study illustrates, Somatotype of the Endomorphs, Mesomorphs and Ectomorphs were the same. As a result, coaches can plan wrestlers` training programs and review of techniques based on anthropometric and physiologic data driven from their sports performances.Besides, wrestlers could be well-informed about their performance. Moreover, aforesaid information could be beneficial to wrestling federations and all other organizations contributing the wrestling federation while holding talent identification programs and recognizing young wrestlers.